TUC Centenary Institute of Occupational Health, 1978 (1978)
1978 1960-2000 "TUC Centenary Institute of Occupational Health, 1978" [T0431.jpg], 1978 In partnership with the London School of Hygiene and Tropical Medicine, the TUC established an Institute of Occupational Health in 1968. The Institute promoted research and epidemiological surveys of occupational health and also offered an information and investigatory service for unions. The TUC ended its link with the institute in 1988.